The effect of inpatient user charges on inpatient care - Jana Votapkova (Charles University in Prague, Institute of Economic Studies (IES), 2020)
The essay assesses the infuence of inpatient user charges in the Czech Republic on the amount of inpatient hospital care provided, namely the number of patient days. We apply the difference-indifferences approach on a panel of 76 general hospitals in 2008-2009. The introduction and subsequent partial reimbursement of user fees charged on an inpatient day in the Czech Republic satisfies the criteria of a natural experiment - the decision to reimburse patients for user charges applied to hospitals under the control of the Social Democratic (éCSSD) regional governments in the year 2009, and was unrelated to other hospital characteristic. Our treatment group comprises hospitals where patients could ask for reimbursement, i.e. user charges were effectively abolished. The control group covers hospitals where it was not possible to get reimbursement. The base year is 2008 when user charges were introduced. The observed effect of user-charge abolition was small and marginally significant (between 2.7 % and 4.1 %) having controlled for exogenous hospital and regional characteristics.
Keywords: I12; I18; 330; Cost-sharing; inpatient care; difference-in-difference; Czech Republic